The Evolution of Dendritic Cell Immunotherapy against HIV-1 Infection: Improvements and Outlook - Hager Mohamed; Vandana Miller; Stephen R. Jennings; Brian Wigdahl; Fred C. Krebs (Journal of Immunology Research)
Dendritic cells (DC) are key phagocytic cells that play crucial roles in both the innate and adaptive immune responses against the human immunodeficiency virus type 1 (HIV-1). By processing and presenting pathogen-derived antigens, dendritic cells initiate a directed response against infected cells. They activate the adaptive immune system upon recognition of pathogen-associated molecular patterns (PAMPs) on infected cells. During the course of HIV-1 infection, a successful adaptive (cytotoxic CD8+ T-cell) response is necessary for preventing the progression and spread of infection in a variety of cells. Dendritic cells have thus been recognized as a valuable tool in the development of immunotherapeutic approaches and vaccines effective against HIV-1. The advancements in dendritic cell vaccines in cancers have paved the way for applications of this form of immunotherapy to HIV-1 infection. Clinical trials with patients infected with HIV-1 who are well-suppressed by antiretroviral therapy (ART) were recently performed to assess the efficacy of DC vaccines, with the goal of mounting an HIV-1 antigen-specific T-cell response, ideally to clear infection and eliminate the need for long-term ART. This review summarizes and compares methods and efficacies of a number of DC vaccine trials utilizing autologous dendritic cells loaded with HIV-1 antigens. The potential for advancement and novel strategies of improving efficacy of this type of immunotherapy is also discussed.